Low Relative Sit‐to‐Stand Power Is Associated With the Development of Adverse Health Outcomes: A 5‐Year Longitudinal Study - Mikel Garcia‐Aguirre; Ivan Baltasar‐Fernandez; Julian Alcazar; Ana Alfaro‐Acha; F. A. Bareiro‐Quiñonez; Ignacio Ara; Leocadio Rodriguez‐Mañas; Francisco J. Garcia‐Garcia; Luis M. Alegre (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Relative sit‐to‐stand (STS) power has emerged as a key biomarker of aging due to its strong association with adverse health outcomes such as frailty or disability. Thus, this study aimed to evaluate the association between low baseline relative STS power with the development of adverse health outcomes. Methods A total of 839 community‐dwelling older adults (65–91 years; 42% men) from the Toledo Study for Healthy Aging were assessed at baseline and after 5 years of follow‐up. Relative STS power was assessed using the 30‐s STS test and Alcazar's equation. Adverse conditions considered encompassed frailty (evaluated using the frailty trait scale 5 [FTS5] or frailty phenotype [FP]), disability in basic (BADL; Barthel index) and instrumental activities of daily living (IADL; Lawton and Brody scale), cognitive impairment (mini‐mental state examination), depression (geriatric depression scale) and medication use. Results At baseline, people with low relative STS power (461 participants) had significantly higher FTS5 (+5.9 points), FP (+0.56 criteria), disability in BADL (−0.1 points) and IADL (−0.7 points), cognitive impairment (−1.3 points) and medication use (+0.9 medications) than older adults with normal relative STS power (all p < 0.05). In contrast, no significant differences were observed at baseline in GDS (p > 0.05). Low baseline relative STS power was significantly associated with the incidence of frailty FTS5 (OR [95% CI] = 2.51 [1.26–5.03]; p = 0.009), disability in BADL (OR [95% CI] = 1.70 [1.13–2.56]; p = 0.011) and IADL (OR [95% CI] = 1.79 [1.06–3.02]; p = 0.030) and increased medication use (OR [95% CI] = 1.51 [1.10–2.07]; p = 0.011) during the follow‐up. No association was found with the incidence of frailty by FP (OR [95% CI] = 1.71 [0.75–3.93]; p = 0.202), depression (OR [95% CI] = 1.29 [0.85–1.98]; p = 0.236) or cognitive impairment (OR [95% CI] = 1.38 [0.86–2.21]; p = 0.178). Conclusion Participants with low relative STS power exhibited worse baseline and 5‐year follow‐up values in frailty, BADL and IADL disability, cognitive impairment and medication intake. Low relative STS power was also associated with a higher probability of future frailty, disability in BADL and IADL and increased medication use.